"It's Like Being Back in GCSE Art"-Engaging with Music, Film-Making and Boardgames. Creative Pedagogies within Youth Work Education - Frances Howard (MDPI AG, 2021)
Creative pedagogies within youth work practice are well established. Practitioners working with young people are often called upon to utilise their own personal and professional 'toolboxes', as a way of supporting 'Creative Arts Youth Work'. However, within Higher Education (HE), creative methods for teaching and learning within the university context are often overlooked. The problem posed by this article is: how can HE 'catch-up' with more advanced pedagogies in the field of practice? Despite a recent focus on the personalisation of learning within HE, how can arts-based pedagogies, including digital storytelling, be drawn upon to enhance the learning experience? This article reports on three areas of pedagogical innovation engaged with by students undertaking the Youth Studies degree at Nottingham Trent University. Three experimental initiatives are explored, which assisted in educating informal educators, through creative learning techniques. Engaging with music, film-making and boardgames are given as examples of creative pedagogy, reporting on both my own practical experience in organising these activities and student feedback. Results showed that the symbiosis of creative pedagogies with relational and experiential learning, key tenets of youth work practice, offered expressive and authentic conditions for learning that are based upon student's experiences. Therefore, there is much to learn from youth work courses within HE, not only in terms of engaging and encouraging students through creativity, but also setting the scene for the future of creative youth work practice.